2010
DOI: 10.1007/s10658-010-9627-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of race-specific resistance against Bremia lactucae in natural populations of Lactuca serriola

Abstract: A metapopulation approach was applied to population studies of a common weed, Lactuca serriola (prickly lettuce). Seedlings grown from seed samples collected from 752 individual L. serriola plants in 50 populations occurring along an east-to-west transect across four European countries (Czech Republic, Germany, Netherlands and United Kingdom) were screened for resistance to 10 common races of Bremia lactucae. Based on the recorded reaction patterns, host individuals were characterized into specific resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…Population genetic analysis by D' Andrea et al (2009) revealed that the British populations were mainly dominated by one single genotype. This also strongly supports data about variability of European L. serriola populations expressed by AFLP (Lebeda et al, 2009b) and the distribution of race-specific resistance to Bremia lactucae (Lebeda and Petrželová, 2007;Lebeda et al, 2008;Petrželová and Lebeda, 2011). In relation to the studied countries, achenes from inland (Czech and German populations) create one homological group, which is identified by shorter beaks than achenes from the Dutch and United Kingdom populations (Table 7c and Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Population genetic analysis by D' Andrea et al (2009) revealed that the British populations were mainly dominated by one single genotype. This also strongly supports data about variability of European L. serriola populations expressed by AFLP (Lebeda et al, 2009b) and the distribution of race-specific resistance to Bremia lactucae (Lebeda and Petrželová, 2007;Lebeda et al, 2008;Petrželová and Lebeda, 2011). In relation to the studied countries, achenes from inland (Czech and German populations) create one homological group, which is identified by shorter beaks than achenes from the Dutch and United Kingdom populations (Table 7c and Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, a study using ten downy mildew isolates against L. serriola sampled from 50 natural populations along a transect stretching from the United Kingdom to the Czech Republic similarly showed an unequal distribution of race-specific resistances among European regions. Diversity in that study increased from west to east, while high disease incidence and high overall resistance were found only in populations from the Czech Republic (Petrželová and Lebeda, 2011). Diversity patterns on downy mildew resistance were in line with the results of molecular studies for L. serriola, revealing increasing levels of diversity from Western to Eastern Europe (Lebeda et al, 2009;van de Wiel et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
“…The results show large variation both amongst and within individual populations and countries. A clear gradient of increasing uniformity of race-specificity was detected when moving from central to western Europe, as well as a slight decrease in the diversity of resistance phenotypes (Petrzelova & Lebeda 2010). Forty-five resistance phenotypes against B. lactucae were found in 16 L. serriola populations across the Czech Republic.…”
Section: R E G I O N a L P A T T E R N S O F R E S I S T A N C Ementioning
confidence: 95%